The ionization of pharmacologically active compounds in the presence of differently charged micelles as biomembrane mimetic systems - Popović Nikolić, Marija; Popović, Gordana; Nikolić, Katarina (Archives of Pharmacy, 2022)
The knowledge of drugs ionization is necessary for prediction of their pharmacological behavior and pharmacokinetic parameters. However, the distribution of equilibrium forms could differ from expected one if the estimation is made exclusively based on pKa vales observed in “pure” water. It is necessary to investigate the ionization of drugs in conditions which is known to mimic the biological membranes such as the micellar solutions of surfactants. The pKa values of pharmacologically active compounds (antihypertensives, antimicrobial drugs, antihistamines) have been potentiometrically determined under the same conditions (25 °C, ionic strength 0.1 M NaCl) with and without micelles, anionic (SDS), cationic (CTAB), nonionic (TX-100, Brij 35). Experimental results were analyzed in program Hyperquad. Significant shift in protolytic equilibria (∆pKa) were observed for aliphatic amino (-2.80 to +0.87), aromatic amino (-1.99 to +1.44), and carboxylic (-0.92 to +1.90) functional groups. The anionic and cationic expressed higher effect on ionization comparing to nonionic micelles. The presence of micelles caused the change in distribution of equilibrium forms especially on pH values of biopharmaceutical importance where the content of ionized form was changed in range from -74% to +66% comparing to “pure” water. The ionization groups of drugs are involved in interactions with charged or polar surface of micelles which could be observed in terms of physiological conditions. Result showed that general pattern of ionization of drugs in micellar media could not be anticipated so it is necessary to be experimentally investigated for each individual drug.